High-frequency multibeam echo-sounder measurements of seafloor backscatter in shallow water: Part 1 - Data acquisition and processing. - Parnum, Iain; Gavrilov, Alexander (Society for Underwater Technology, 2011)
Methods for processing multibeam echo-sounder (MBES) bathymetry data are well established, however, there is no universal and established approach to processing and interpretation of MBES backscatter data. The aim of this paper is to (1) detail the different backscatter logging methods implemented in modern high-frequency MBES systems used primarily in shallow water; (2) describe and suggest appropriate methods of data processing; and (3) discuss likely errors and artefacts expected from MBES backscatter processing. These issues are illustrated using data collected with a Reson SeaBat MBES in coastal shelf areas of Australia, although the methods and errors discussed are relevant to other high-frequency shallow-water MBES systems. Production of backscatter mosaics and analysis of backscatter for seafloor classification using MBES data are considered in Part 2 – Mosaic production, analysis and classification (Parnum and Gavrilov, 2011), published alongside this paper.